Experimental investigations of methane hydrate in sediment suspensions - Radhika, Ikkurti; S. R. Prasad, Pinnelli; Suresh Babu, Devarasetty (International Journal of Engineering and Technology, 2018)
Methane hydrate structural stability and formation, were studied in water suspensions with synthetic clay (44.17nm),SiO2(60.62nm) and zeolite (35.08nm) at different weight percentages (1wt%,10wt%,20wt%) in isochoric method using stirred autoclave. The for- mation kinetics in these sediments greatly differs from those of the bulk hydrate owing to surface and capillary effects in the pores. It has been confirmed that hydrate formation in confined pores is severely restricted due to increased inner capillary pressure. Further- more in principle , the clay particles suspended in water play a negative role in structuring the crystalline hydrate .More specifically, even though the addition of clay enhances the hydrate yield insignificantly, from our results, the addition of sediments did not affect the phase equilibrium much because water exists in excess around clay particles and therefore the hydrate formed in the bulk water phase is much more dominant than that in the pores.
Keywords: Gas Hydrates; Methane; Phase Equilibrium.